Nomophobia and self-reported smartphone use while driving: An investigation into whether nomophobia can increase the likelihood of illegal smartphone use while driving. (October 2020) - Kaviani, F.; Young, K.L.; Robards, B.; Koppel, S.
Highlights: On average, Victorians exhibit moderate level of nomophobia. 20% of drivers are unaware of laws concerning smartphone use while driving. 37% of drivers have used a smartphone illegally in past 31 days. Nomophobia does not usefully predict illegal smartphone use while driving. Knowledge of law and age group predict illegal smartphone use. Abstract: In Australia, illegal smartphone use while driving is on the rise, increasing the likelihood drivers could be distracted and crash. Smartphones avail users a sense of belonging, connectedness, and access to information. As such, the sensation of being without one's smartphone has developed into the prevalence of nomophobia, defined as the fear and anxiety associated with being without smartphone. The aim of the current study was to specifically examine the relationship between smartphone use while driving and nomophobia by 1) determining the types and frequency of illegal phone use while driving and, 2) exploring the relationship between nomophobia and illegal phone use while driving. The sample consisted of 2, 774 Victorian smartphone users (47.0% male) with a valid driver's licence. Driver's nomophobia levels were measured using the Nomophobia Questionnaire (NMP-Q), while driver's smartphone use was measured using an original scale developed by the authors. A binary logistic regression was conducted which showed that the longer average time spent per day on a smartphone and a lack of knowledge of the mobile phone road law were the strongest positive predictors of illegal use (OR = 1.32, 95% CI = 1.09–1.60; OR = 1.84, 95% CI = 1.48–2.28, respectively). However, only one nomophobia factor (i.e., access to information) significantly predicted illegal smartphone use (OR = 1.06, 95% CI = 1.04–1.09). Smartphone use is a complex and contextual behaviour, therefore, focusing on the fear of being without in dependency overlooks the nuances of the need to be with . This study offered several practical interventions that may mitigate illegal smartphone use and reduce the likelihood of crashes among Victorian road users.